Some Effects of Purified Autoprothrombin C in Blood Clotting - Müller-Berghaus, G; Seegers, W. H (Thrombosis and Haemostasis, 1966)
Purified autoprothrombin C was added to rabbit blood or recalcified plasma in order to measure the exact influence on clotting time. At a concentration of 10 u of autoprothrombin C per ml blood there was clotting in 13 sec. At that concentration recalcified plasma clotted in 7 to 8 sec. In the acceleration of the whole blood clotting time with autoprothrombin C, the effect was greater in glass tubes than in silicone coated tubes. The difference was probably due to lipids from platelets. With autoprothrombin C at a concentration of 10 u/ml reaction mixture, the prothrombin time and partial thromboplastin time of plasma was brought down to 3 to 4 sec. The partial thromboplastin time supplied the most sensitive conditions for detecting autoprothrombin C activity. Less than 2 × 10−5 micrograms of autoprothrombin C were detected. Rabbits that were treated with Coumadin had their prothrombin concentration reduced to 9 u/ml plasma, as measured by two-stage analysis. Such plasma yielded twice as much thrombin when purified autoprothrombin C and purified Ac-globulin were used in the assay to determine the thrombin potential. Even when the prothrombin concentration was brought to low levels with Coumadin a partial thromboplastin time or prothrombin time of 7 sec was easily obtained by using autoprothrombin C as procoagulant. The important effect of Coumadin or related drugs is the reduction of prothrombin concentration. This involves a lowering of the autoprothrombin C potential as well as the thrombin potential of plasma, and also the amount of inhibitor that can be obtained from prothrombin.Normal blood was found to contain prethrombin in small amounts as well as prothrombin. The synthesis of prothrombin was stopped with Coumadin and it is likely that the residual prothrombin was in part utilized by degradation to prethrombin, inhibitor and autoprothrombin III. At the height of the anticoagulant effect the prethrombin concentration was higher than the prothrombin concentration. With the resumption of prothrombin synthesis, when vitamin K was given, it may be that prethrombin, inhibitor, and autoprothrombin III was first produced in the liver and some of the latter entered the blood stream to compensate for substrate deficiency. Free autoprothrombin III would account for the short prothrombin time observed before prothrombin concentration rose.